Plädoyer für Förderung der Vorlesekompetenz im DaF-Bereich – potenzielle Verfahren zur Stärkung der Leseflüssigkeit - Żytyńska, Małgorzata (2022)
This article deals with methods of oral-reading, which should improve reading competence and reading fluency. Important when reading aloud are the following components: decoding, accuracy, automaticity, fluency, reading speed and text comprehension. And all these components should be practised with the following oral-reading methods: repeated reading, assisted reading or paired repeated reading. All these aloud-reading methods contribute to the increase of reading competence. Therefore, they should be applied also in German as a foreign language lessons.
Keywords: reading competence; reading training; reading fluency; reading speed; prosodic parsing